Insulinotropic Potential of Amphibian Antimicrobial Peptides Isolated from the Skin Secretions of Bornean Frogs - Amera, A. M. Abdalnabi; Muna, Sabri; Zunika, Amit; Ramlah, Zainudin
Skin secretion of two Bornean frogs, Limnonectes paramacrodon and Pulcharana baramica, were studied for their antimicrobial and insulinotropic properties. Comprehensive techniques were employed to study the characteristics of the antimicrobial peptides (AMPs) isolated from these frogs. The secretions were partially purified using Sep Pak C-18 cartridges, followed by further purification via the FPLC system. The size and purity of the peptides were assessed through SDS-PAGE gel, which revealed the efficacy of FPLC method in the purification of these secreted peptides. The antimicrobial properties of the peptides were assessed using disk diffusion and minimum inhibitory concentration (MIC) assays. Significant zones of inhibition in disc diffusion assay against both E. coli and S. aureus were observed for the peptides from Pulchrana baramica, while no inhibition zones were observed for Limnonectes paramacrodon, indicating the stronger antibacterial activity of the former ranid’s skin peptides. The MIC results showed higher potency of AMPs from Pulchrana baramica when compared to the peptides from Limnonectes paramacrodon. In terms of cytotoxicity, purified AMPs from P. baramica frogs induced over 50% blood cell lysis, suggesting the adverse effect of the peptides against the cell membranes of mammalian erythrocytes. The insulinotropic effect of AMPs from these two Bornean frogs were studied using the HIT-T15 cells. AMPs of both frog species from two different families were able to trigger insulin secretion from the pancreatic beta cells lines. Statistical analysis indicated a significant difference (p < 0.05) from P. baramica, while Limnonectes paramacrodon effect was not significant (p > 0.05). The current findings demonstrated the diverse potency of antimicrobial peptides from the skin secretion of frogs from different families. These observations suggest marked differences in the structures, compositions and physicochemical properties of these AMPs, which may relate to their habitat and microbial pressure as well as their lineage and evolution.